SOFT SYSTEMS METHODOLOGY PADA PENGEMBANGAN BANDAR UDARA PROVINSI SULAWESI BARAT - Prasadja Ricardianto; Salahudin Rafi; Muhammad Rifni (Institut Transportasi dan Logistik Trisakti, 2017)
The purpose of the study is to identify airport development plan towards Public Transport Policy based on Airport Development Blue Print with Soft System Methodology (SSM) in West Sulawesi Province. The study is qualitative by applying Soft System Methodology (SSM) with root definition component, constructing images known as rich picture and CATWOE six-element analysis. The data is collected by focus group discussions and in-depth interviews using purposive sampling technique. The results show airport development concept based on seven stages of Transport Public Transport Policy on Soft System Methodology (SSM) basis.